Populations of Select Cultured and Uncultured Bacteria in the Rumen of Sheep and the Effect of Diets and Ruminal Fractions - Jill Stiverson; Mark Morrison; Zhongtang Yu (International Journal of Microbiology)
The objective of this study was to assess the importance of select cultured and uncultured bacteria in the rumen by quantifying their populations and the effect of diets and ruminal fractions. Full-length 16S rRNA gene (rrs) sequences were recovered from rumen samples using specific primers designed from partial sequences recovered previously. Five uncultured bacterial operational taxonomic units (OTUs) were quantified using specific quantitative PCR (qPCR) in fractionated ruminal samples from sheep fed either hay alone or hay plus corn. Species Fibrobacter succinogenes, Ruminococcus albus, R. flavefaciens, Ruminobacter amylophilus, Selenomonas ruminantium, and Mitsuokella multacida and genera Butyrivibrio and Prevotella were also quantified as comparison. The full-length rrs sequence improved taxonomic assignments of partial rrs sequences. Genus Prevotella had the greatest abundance. Of the three major cultured cellulolytic species, R. flavefaciens was most abundant, followed by R. albus and F. succinogenes. The five uncultured bacterial OTUs, classified to genus Acetivibrio, genus Allobaculum, family Ruminococcaceae, order Clostridiales, or class Clostridia, had abundance comparable to that of the above species of genera except Prevotella. Corn supplementation and fractions affected distribution of the rumen bacteria, but to a limited extent. When compared to the qPCR data, sequence frequencies in the rrs clone libraries tended to overestimate the abundance of the bacteria represented. This study showed that abundance and population dynamics of uncultured bacteria can be quantified by specific qPCR, which complements the results of rrs clone libraries. This study also revealed that some uncultured bacteria might be as important as some of the well-characterized bacteria in the rumen. The approach used should be applicable to assess the abundance and potential importance of uncultured bacteria in other environments.